Pseudomyxoma peritonei and mucocele of vermiform appendix simulating right adnexal mass - Wilczyński, Miłosz; Szpakowski, Marian; Laskowski, Jarosław; Krawczyk, Tomasz; Krawczyk, Andrzej; Radosław Wilczyński, Jacek (Menopause Review/Przegląd Menopauzalny, 2010)
We present a case of a 51-year-old woman who suffered from persistent right lower abdominal pain. Ultrasound examination revealed two lesions in the area of right adnexa. A suspicion of right adnexal cyst was made. Laparoscopy showed that patient was affected by an early stage of pseudomyxoma peritonei (PMP) resulting from a ruptured mucocele of the vermiform appendix. This condition is very rare, however, due to its localization and not specific clinical manifestation it should be taken into consideration in the differential diagnosis of adnexal masses.